How do patients with diabetes report their comorbidity? Comparison with administrative data - Hoffmann J; Haastert B; Brüne M; Kaltheuner M; Begun A; Chernyak N; Icks A (Clinical Epidemiology, 2018)
Jonas Hoffmann,1,* Burkhard Haastert,2,* Manuela Brüne,1 Matthias Kaltheuner,3 Alexander Begun,1 Nadja Chernyak,4 Andrea Icks1,4,5 1Institute of Health Services Research and Health Economics, German Diabetes Center, Düsseldorf, Germany; 2mediStatistica, Neuenrade, Germany; 3Specialized Diabetes Practice Leverkusen, Leverkusen, Germany; 4Faculty of Medicine, Centre for Health and Society, Institute of Health Services Research and Health Economics, Heinrich-Heine University Düsseldorf, Düsseldorf, Germany; 5German Center for Diabetes Research, Ingolstädter Neuherberg, Germany *These authors contributed equally to this work Aims: Patients with diabetes are probably often unaware of their comorbidities. We estimated agreement between self-reported comorbidities and administrative data. Methods: In a random sample of 464 diabetes patients, data from a questionnaire asking about the presence of 14 comorbidities closely related to diabetes were individually linked with statutory health insurance data. Results: Specificities were >97%, except cardiac insufficiency (94.5%), eye diseases (93.8%), peripheral arterial disease (92.6%), hypertension (90.9%), and peripheral neuropathy (85.8%). Sensitivities were <60%, except amputation (100%), hypertension (83.1%), and myocardial infarction (67.2%). A few positive predictive values were >90% (hypertension, myocardial infarction, and eye disease), and six were below 70%. Six negative predictive values were >90%, and two <70% (hypertension and eye disease). Total agreement was between 42.7% (eye disease) and 100% (dialysis and amputation). Overall, substantial agreement was observed for three morbidities (kappa 0.61–0.80: hypertension, myocardial infarction, and amputation). Moderate agreement (kappa 0.41–0.60) was estimated for angina pectoris, heart failure, stroke, peripheral neuropathy, and kidney disease. Factors associated with agreement were the number of comorbidities, diabetes duration, age, sex, and education. Conclusions: Myocardial infarction and amputation were well reported by patients as comorbidities; eye diseases and foot ulceration rather poorly, particularly in older, male, or less educated patients. Patient information needs improving. Keywords: diabetes comorbidities, self-report, agreement, patient information